Trolldom mot kongens skip 1589 og transnasjonal overføring av idéer - Willumsen, Liv Helene (Historisk Tidsskrift, 2021)
Witchcraft against royal Danish ships in 1589 and transnational transfer of ideas From the late 1400s onwards, the learned doctrine of demonology exerted an ever-growing influence on witch trials throughout Europe. This article studies the alleged witchcraft performed against a royal Danish fleet that was to carry Princess Anne across the North Sea to her husband, King James VI of Scotland, in the autumn of 1589. Violent storms prevented the transfer and the fleet had to seek shelter in Norway. King James eventually sailed to Norway, married his bride and paid an extended visit to Denmark. Before his departure from Denmark, in the spring of 1590, a series of witch trials started in Copenhagen. These trials, and the transfer of ideas about witchcraft ideas coming to the fore during the accused persons’ confessions, are here studied on the basis of court records and state papers related to correspondence between the courts in Denmark, England and Scotland, as well as diplomatic correspondence from the three countries. In addition to the Copenhagen witchcraft trials, attention is paid to the North Berwick trials in Scotland, 1590-1591, where demonological ideas, influenced by the preceding trials in Copenhagen, appear for the first time in Scottish witchcraft trials. The article sheds light on the content of witchcraft trials, the routes for transmission of witchcraft ideas, and on the contemporary context for interpreting notions of witchcraft.